2023
DOI: 10.18332/tid/157205
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with an increase in alcohol consumption and tobacco use during the COVID-19 pandemic: A cross-sectional study of data from 105 countries

Abstract: INTRODUCTION The COVID-19 pandemic has inevitably led to monumental challenges, and alcohol drinking and tobacco use have unlikely been spared. This cross-sectional survey reports on factors associated with an increase in alcohol drinking and tobacco use during the COVID-19 pandemic. METHODS An online survey conducted in 2020, generated data from 14899 adults residing in 105 countries. Dependent variables were changes in alcohol drinking and tobacco use. Independent variables were age, sex, education level, j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…This study found that college students have strong ILoC. It has been confirmed by previous studies showing that tobacco users in both academic settings and workplaces are predominantly internal [ 11 - 16 ]. Healthcare professionals should consider the consistency of smokers in numerous studies, including the one above, to design successful interventions to affect patients.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study found that college students have strong ILoC. It has been confirmed by previous studies showing that tobacco users in both academic settings and workplaces are predominantly internal [ 11 - 16 ]. Healthcare professionals should consider the consistency of smokers in numerous studies, including the one above, to design successful interventions to affect patients.…”
Section: Discussionsupporting
confidence: 85%
“…Policy and environmental issues are thought to significantly impact patients with internal LoC, which others have evaluated very strongly [ 23 ]. This is logical, as managers and employers often formulate regulations where students smoke [ 16 ]. “Policies to limit smoking behavior in the workplace by minimizing smoking opportunities, reducing incentives to smoke, and improving social support for quitting,” argues Moskowitz.…”
Section: Discussionmentioning
confidence: 99%
“…If data is pooled from many countries, data may become heterogenous and possibly non-representative if the number of participants per country is low. For instance, in the survey by Quadri et al (2023), the average number of participants per country was 142. Pooled data may also become difficult to interpret when number of participants varies greatly between countries.…”
Section: Discussionmentioning
confidence: 99%
“…Economic hardship could therefore also increase alcohol consumption due to psychological distress. One survey conducted with 14,899 residents from 105 countries suggested that job losses and lost or reduced wages may have increased alcohol consumption (Quadri et al, 2023). But in many countries, alcohol consumption during the first months of the pandemic seemed to have decreased rather than increased (Kilian et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation